El Manual Para el Pueblo (The Manual for the People): a pictorial aid for community health workers to identify surgical conditions - Sebastian Gualy, BS; Christopher Herrera, BS; Bessy Colman, MD; Alex Guerrero; Nydia Betanco; Katie Magoon, MPA; Jordan Swanson, MSc (Elsevier, 2019)
Background: Access to safe, effective, and affordable surgical care is a pressing contemporary public health issue. Deaths from surgically treated conditions exceed those from HIV, tuberculosis, and malaria combined. Community outreach is a potential driver of access to surgical treatment, yet education among community health workers (CHWs) about such conditions is insufficient. Here, we describe the development and testing of a picture-based curriculum-El Manual Para el Pueblo (The Manual for the People)-to help CHWs to identify and refer surgical conditions in a largely illiterate population. Methods: Central American rural multi-ethnic indigenous groups and surgical providers provided context-specific expertise and advice for the development of El Manual Para el Pueblo, established in 2017. During a pilot implementation in July, 2018, the Ministry of Education and a local community leader recruited groups of CHWs, parents in the communities, and groups of students from the Olancho department of Honduras. We assessed participants before and after the teaching programme for situational problem-solving. Participants completed quantitative surveys to measure the efficacy of an accompanying curriculum on the scheme and iconography of the manual; we also collected qualitative data from participants about the utility of the programme for their practice patterns. Findings: The surgical manual includes 13 chapters with 133 different medical and surgical conditions represented. For the surveys, participants used three sample pages of the manual to answer the questions. We included 403 participants; 68% were women and mean age was 26 years. Overall, 245 participants (61%) had scores of 75% or more on the pre-intervention survey and 170 (42%) had scores of 85% or more. Manual understanding and utilisation abilities improved from pre-intervention mean score of 15·37 (SD 3·10) to 15·91 (3·09) post-intervention out of a maximum score of 20 (p<0·0001). Results of the qualitative assessment showed that there is a need for the manual, that the manual is readable, and that CHWs are willing to use the manual. 378 participants (94%) identified a time in their life when access to a hospital was required; 389 (96%) found the manual easy to read, and 398 (98%) would use this manual again. Interpretation: Surgical disease burden is one of the most pressing public health problems globally and there is an important opportunity to improve care for the 5 billion people who lack adequate access to surgical care. El Manual Para el Pueblo is one such tool. Our data suggest that this curriculum can be an effective educational tool for improving on-the-ground understanding of the triage of surgical and medical disease, as well as techniques for best use of the manual. Finally, our study reinforces the need to invest in education for local personnel when implementing similar interventions to achieve the maximum societal effects. Funding: Operation Smile, Agnew Surgical Society at the Perelman School of Medicine.